2006
DOI: 10.1207/s15327663jcp1603_2
|View full text |Cite
|
Sign up to set email alerts
|

Reflective and Impulsive Determinants of Consumer Behavior

Abstract: This article describes a dual‐system model of consumer behavior. This model is based on the assumption that all human behaviors are a joint function of reflective and impulsive mechanisms. Those mechanisms have different principles of operation but contribute to the act of buying. However, the relative contribution of impulsive and reflective processes depends on personal and contextual circumstances. The operation and interaction of the 2 systems at different stages of information processing is described and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
202
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(215 citation statements)
references
References 108 publications
(133 reference statements)
7
202
0
6
Order By: Relevance
“…Such assumption is corroborated by evidence suggesting that purchasing more durable or expensive products or making purchases for which consumers expect to be held accountable by others, lead to more careful information processing (Ben-Zur & Breznitz, 1981), smaller impact of peripheral cues (Petty, Cacioppo, & Schumann, 1983) and more reflective decisions (Strack & Deutsch, 2006).…”
Section: Study 2: Influence Of Time Pressure In Service Choicesmentioning
confidence: 84%
“…Such assumption is corroborated by evidence suggesting that purchasing more durable or expensive products or making purchases for which consumers expect to be held accountable by others, lead to more careful information processing (Ben-Zur & Breznitz, 1981), smaller impact of peripheral cues (Petty, Cacioppo, & Schumann, 1983) and more reflective decisions (Strack & Deutsch, 2006).…”
Section: Study 2: Influence Of Time Pressure In Service Choicesmentioning
confidence: 84%
“…The latter, in contrast to impulsivity, does not need to be spontaneous, can involve reflection, and is not necessarily induced by urges. Recent technological innovations such as the cash machine, home-shopping television programs, and the Internet facilitate quick and effortless consumption, so that today the opportunities to buy impulsively occur more often than ever before (Strack et al, 2006;Vohs and Faber, 2007). Additionally, dramatic increases in individual disposable incomes and credit facilities have supported the rise of impulsive consumption (Dittmar and Drury, 2000).…”
Section: Impulsive Consumptionmentioning
confidence: 99%
“…System 2 is slow, rule-based, controlled, and comprises the abilities of willpower and cognition. Other notations for the two systems include, respectively, desire and willpower (Hoch and Loewenstein, 1991), the hot system and the cold system (Metcalfe and Mischel, 1999), and impulsive and reflective mechanisms (Strack et al, 2006). Whereas System 1 is assumed to exist in both animals and humans, System 2 is unique to humans (at least in its disproportionately large size).…”
Section: The Behavioral Economic Perspective: Two Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies have revealed that a high level of involvement facilitates systematic processing of an ad or information about the product: highly involved participants read questions and texts with more elaboration (Chaiken & Maheswaran, 1994;Maheswaran et al, 1992;Posavac, Sanbonmatsu, Kardes & Fitzsimons, 2004) and they tend to base their judgments on facts, therefore, cues such as temporary emotional state, brand personality, or previous judgments are depreciated (Bosmans & Baumgartner, 2005;Higgins, 1996;Maheswaran et al, 1992;Strack, Werth & Deutsch, 2006). Conversely, a low level of involvement favors heuristic processing that biases judgment towards the influence of irrelevant stimuli, and less involved participants put less effort into answering while relying on unproven and unjustified premises (Aaker & Keller, 1990;Bosmans & Baumgartner, 2005;Kardes, 2006;Keller & Bless, 2005;Maheswaran & Chaiken, 1991;Strack et al, 2006;Thomson et al, 2005).…”
Section: Task Involvement As a Moderator Of Brand Effectmentioning
confidence: 99%